Avaliação dos efeitos de dieta acrescida de colesterol em modelos experimentais da Doença de Alzheimer - Suelyn Koerich (2022)
Alzheimer's disease (AD) is the most common age-related neurodegenerative disease and, despite its relevance, the pathophysiological mechanisms are not completely understood. Recently, it has been suggested that cholesterol homeostasis is involved in the pathophysiology of AD. Thus, the aim of the present study was to investigate the effects of a diet on increased cholesterol in experimental models of AD. For this, male C57BL/6 mice, aged 8 weeks, were treated with a diet plus 1.25% cholesterol or a control diet for four months, and then received intrahippocampal microinjection of Aβ1-42 (400 pmol) or sterile saline solution. Additionally, we evaluated the effects of diet in the transgenic model for AD. Male and female APP/PS1 animals, 10 months of age, were treated for four months with a diet plus 1.25% cholesterol or a control diet. For cognitive assessment, we used the novel object recognition test (ORT) in all animal models. In addition, we evaluated neuronal viability, microgliosis, and labeling of amyloid plaques in the hippocampus of male APP/PS1 animals. Furthermore, we evaluated the effects of diet on peripheral parameters. We demonstrated that a diet supplemented with cholesterol was able to prevent cognitive impairment induced by intrahippocampal microinjection of Aβ1-42 and to improve cognitive impairment in APP/PS1 animals. This effect in APP/PS1 animals was accompanied by a reduction in amyloid plaque labeling and hippocampal microgliosis. In addition, there was no change in weight, adiposity index, and serum levels of total cholesterol and triglycerides. Finally, dietary cholesterol increased the liver weight/body weight ratio and the concentration of total hepatic lipids, in addition to decreasing SOD activity in the intrahippocampal microinjection model. Taken together, these results demonstrate that animals fed only with cholesterol, without adding fat to the diet, show cognitive improvement, especially that which depends on hippocampal functioning. This improvement could be associated with both the reduction of plaque deposition and microgliosis. Although the mechanism has not been established, it can be suggested that cholesterol metabolism is an important factor in the development of AD.